'And those who live, how shall I tell their fame?' Historical pageants, collective remembrance and the First World War, 1919–391. Issue 249 (8th June 2017) - Bartie, Angela; Fleming, Linda; Freeman, Mark; Hulme, Tom; Readman, Paul; Tupman, Charlotte
Abstract: This article examines the ways in which the First World War was represented in historical pageants during the interwar period. Pageants in this period are often overlooked as sites of commemoration and dramatic representation. Three types of pageant are identified: those that portrayed the war hyper‐realistically, those which relied on symbolism and allegory to convey messages about war and peace, and those which sought to incorporate the war into the longer histories of the communities whose pasts they depicted. The article argues that 'traditional' forms of representation of the past proved to be resilient features of popular commemoration and remembrance.